The Shamer's war - Kaaberbol, Lene (The Shamer chronicles, 2006)
Dina, a Shamer, and her friend Nico, the legitimate heir to the lordship of Dunark, lead a dangerous rebellion against Drakan, the ruthless Dragon Lord who is hunting down Shamers to burn at the stake.